2019
DOI: 10.21149/9858
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la dependencia física y psicológica al tabaco en fumadores mexicanos adultos, Encodat 2016

Abstract: Objetivo. Evaluar la dependencia física y psicológica de los fumadores mexicanos y su asociación con factores físicos, psicológicos y sociales. Material y métodos. A partir de la Encuesta Nacional de Consumo de Drogas, Alcohol y Tabaco 2016 (n=7 331), se analizó la escala de dependencia física a la nicotina de Fagerström (FTND) y la escala corta de depen­dencia psicológica al tabaco (TAPDSc). Se realizaron análisis bivariados y regresiones logísticas ordinales generalizadas para evaluar los factores asociados.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
6
0
5
Order By: Relevance
“…To evaluate how e-cigarettes influence smoking patterns in Mexico, further research is needed, particularly on how lighter smokers use e-cigarettes. Indeed, psychological dependence47 and potential genetic factors may help to explain low levels of consumption among populations of Mexican heritage,48 whose ancestors used tobacco for centuries before European colonisation of the Americas. Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate how e-cigarettes influence smoking patterns in Mexico, further research is needed, particularly on how lighter smokers use e-cigarettes. Indeed, psychological dependence47 and potential genetic factors may help to explain low levels of consumption among populations of Mexican heritage,48 whose ancestors used tobacco for centuries before European colonisation of the Americas. Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, health personnel are less likely to advise cessation [ 5 ]. However, evidence has shown that nondaily smokers may have a similar or greater physical and psychological dependency and lower intentions to quit than daily cigarette users [ 9 , 41 , 42 ]. Nondaily smokers also perceive lower health risks than daily smokers [ 42 , 43 ], suggesting that media campaigns and cigarette pack warnings may have a limited effect on this group.…”
Section: Discussionmentioning
confidence: 99%
“…To further validate Mexico SimSmoke projections of daily and nondaily smoking, we perform two sensitivity analyses, one assuming half of the original policy effect sizes for nondaily smokers and a second one assuming half of the original effect combined with using the100-cigarettes lifetime screen for defining current smoking prevalence (S1 Report). Assuming half of the original effect, daily smoking projections are unaffected, but SimSmoke nondaily smoking projections in 2016…”
Section: Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Respecto a la dependencia a la nicotina en otros países es elevada en comparación con la población estudiada. En una investigación en México, 82.3% de fumadores diarios y 98.8% de ocasionales reportaron dependencia física leve, mientras que 47.9% y 37.9%, respectivamente, presentaron dependencia psicológica moderada, 21 en cambio los datos obtenidos en el estudio en la población Lenca, el 76.6% tuvo dependencia baja y apenas el 23.4% presento dependencia moderada a la nicotina, ninguno mostro alta dependencia a pesar que se realizó solo en fumadores.…”
Section: Discussionunclassified